DEVELOPMENT OF A UREA BIOSENSOR BASED ON A POLYMERIC MEMBRANE INCLUDING ZEOLITE (Sciences & Technology. A, exactes sciences, 2008)
A urea biosensor has been prepared by covalent biding of urease directly to the surface of an ammonium-sensitive field effect transistor (FET).The NH4+ -sensitive membrane is based on a zeolite-incorporated polymeric membrane biosensor (clinoptilolite). The sensitivity of ammonium  detection is sub-nernstian (32mV/pNH4 +) but the ISFET presents a high selectivity, which is interesting for measurements in biological media. The grafting of urease to the NH4 +-sensitive membrane was permorfed by cross-linking with glutaraldehyde .The sensitivity of the urea ENFET is 15V/purea and this remains stable over 15 days with a detection limit of 3x10-5 M. Finally, in order to test feasibility of the urea biosensor for environmental applications, the remaining activity of the urease was determined after exposure to enzyme inhibiting heavy metals ions such as Hg(II).Using these urea biosensors, a detection limit of less than 5 x 10-8 M was obtained for Hg(II).